TINGKAT KESADARAN PETANI TERHADAP PEMBAYARAN ZAKAT PERTANIAN DI DESA LUNJEN KABUPATEN ENREKANG - Rahim, Abd; Dangnga, Muhammad Siri; B, Abdullah (Universitas Muhammadiyah Makassar, 2021)
The welfare of the farming community is a noble ideal that must be instilled in relation to all activities in society. Lunjen Village, is a village in Enrekang Regency where the majority of the population earns income from agriculture. Agricultural zakat is one of the obligations that must be fulfilled but the partisipation in implementing agricultural zakat is considered to be very lacking in almost all regions. This study aims to see how the awareness of farmers in Lunjen Village in paying agricultural zakat and its relation to the welfare of farmers in terms of the benefits of agricultural zakat on farmers. The method used is descriptive quantitative, with Likkert Scale calculations and Statistical Product and Service Solution (SPSS) analysis, then analyzed to see the benefits that can be felt if farmers routinely pay agricultural zakat. The results of this study found that the level of awareness of farmers is in the high category (61.67%) and the factors that have a positive and significant effect on farmers' awareness are the age factor with a Tcount of 4.322, the education level factor with a Tcount of 5.915 while the income level factor has an effect on negative and significant with a Tcount of -2.307. There are benefits that can be felt by farmers if they routinely pay agricultural zakat, namely that they can achieve farmer welfare, and economic development.